Life cycle assessment of a retail store aquaponic system in a cold-weather region - Elnour, Mugahid; Haller, Henrik; Martin, Michael (Frontiers in Sustainability, 2023)
Alternative food production technologies are being developed to meet the global increase in population and demand for a more sustainable food supply. Aquaponics, a combined method of vegetable and fish production, is an emerging technology that is widely regarded as sustainable. Yet, there has been limited research on its environmental performance, especially at a commercial scale. In this study, life cycle analysis (LCA) was used to assess the environmental impacts of food produced by an urban commercial aquaponic system located next to a retail store in a cold-weather region (Östersund, Sweden). The functional unit (FU) used is 1 kg of fresh produce, which includes cucumber (Cucumis sativus), tomatoes (Solanum Lycopersicum), and Atlantic salmon (Salmo salar). The system boundary is set from cradle to farm or retailer’s gate due to the proximity of the aquaponic system to the retail store. Results were reported employing eight environmental impact categories, including global warming potential (GWP), marine eutrophication (MEU), and cumulative energy demand (CED). According to contribution analysis, the main hotspots of the system are electricity, CO2 enrichment, and heating. Potential areas to mitigate the impact of these parameters were highlighted in this study, including the establishment of symbiotic links to utilize urban waste and by-products. The impact per vegetable or fish produced was partitioned using energy and economic allocation and compared to other common cultivation methods. The yearly harvest from the aquaponic system was also compared to importing these food items from other European countries which showed lower annual greenhouse gas (GHG) emissions for the aquaponic system.